The contribution of posttraumatic stress symptoms to chronic pain adjustment. - Ruiz-Párraga, Gema Teresa; López-Martínez, Alicia Eva (American Psychological Association (APA), 2014)
To examine whether there are differences between non-trauma-exposed, trauma-exposed without posttraumatic stress symptoms (PSS), and trauma-exposed with PSS chronic musculoskeletal pain patients in vulnerability, protective, and pain-adjustment variables; to test the interactive relationship between PSS and the vulnerability and protective psychological variables across pain adjustment in the group of trauma-exposed-patients. Method: 714 patients with chronic musculoskeletal pain were assessed. Of these, 346 patients (244 women and 102 men) completed the study (117 non-trauma-exposed, 119 trauma-exposed without PSS, and 110 trauma-exposed with PSS). The instruments used were the Stressful Life Event Screening Questionnaire Revised, Davidson Trauma Scale, Anxiety Sensitivity Index, Acceptance and Action Questionnaire, Pain Catastrophizing Scale, Fear-Avoidance Beliefs Questionnaire, Pain Anxiety Symptoms Scale, Pain Vigilance and Awareness Questionnaire, Resilience Scale, Chronic Pain Acceptance Questionnaire, Pain Numerical Rating Scale, Roland Morris Disability Questionnaire, and Hospital Anxiety and Depression Scale. Results: Eight ANCOVAs showed that there were statistically significant differences in vulnerability, protection, and pain adjustment variables between the trauma-exposed with PSS patients and the other 2 groups. The moderated multiple regression analyses showed that PSS added a significantly incremental variance to pain intensity, emotional distress, and disability when interacting with vulnerability and protection variables. Conclusion: The current study supports the models of posttraumatic stress and chronic pain, such as the mutual maintenance and the shared vulnerability theories, providing an initial comprehensive framework for understanding the comorbidity of both disorders.
https://openpolicyfinder.jisc.ac.uk/id/publication/3459
Keywords: Estrés postraumático - Efectos fisiológicos; Dolor crónico - Tratamiento; Dolor crónico; Ajuste al dolor; Síntomas de estrés postraumático; Variables psicológicas